Pengaruh Penggunaan Media Audio Visual terhadap Motivasi dan Hasil Belajar Peserta Didik tentang Materi Daur Hidup Hewan - Rima Noriko; Sopiyan Hadi; Andayani Andayani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The very rapid development of science and technology currently requires a country to improve the quality and quality of education in order to be able to compete with countries in the world. One way is to require learning in schools to be in line with developments in science and technology. It is hoped that the application of technology in the learning process can provide greater convenience, independence and interest for students in providing learning materials. This research aims to determine the effect of using audio-visual media on students' motivation and learning outcomes regarding animal life cycle material. The research method used is a quasi-experimental research method with a nonequivalent control group design, where the experimental class is taught with audio-visual media while the control class is taught with a conventional learning model. The research population was all class III students, with sampling using a purposive sampling technique and the research samples were obtained, namely class III OB, totaling 20 students as the control group and class III OD, totaling 20 students, as the experimental group. The research instruments used were learning motivation questionnaires and learning outcomes tests. The questionnaire data analysis technique used is validity and reliability tests, while the test data is tested for validity, reliability, level of difficulty and differentiability of questions. To test the hypothesis, prerequisite tests were carried out using homogeneity and normality tests. After that, hypotheses 1 and 2 were tested using the independent t test, while hypothesis 3 used the MANOVA test. Based on the research that has been carried out, the results obtained are 1) there are differences in student learning outcomes in classes that use learning with audio-visual media, 2) there are differences in the learning motivation of students in classes that use learning with audio-visual media, and 3) there is the influence of media audio visuals on student motivation and learning outcomes.